Bio Farming in Vegetables : Effect of Biofertilizers in Amaranth - Niranjana N S (Department of Agronomy, College of Agriculture, 1998)
An experiment was conducted at the Instruction farm attached to the College of Agriculture, Vellayani, during April - Sept 1996 with objectives of finding out the impact of biofertilizers Arospirillum , AMF and dual inoculation under varying and varied levels of fertilizer on amaranthus. Study also aimed to note the economics of the integrated approach and to identify the best economic combinations which improve yield and quality of amaranth varieties Arun and Kannara local. The study had three controls and two number of replications. The results of the study revealed that yield attributing characters like no: of harvests, yield harvest", marketable yield and dry weight were highest in plots applied with dual inoculation of Azospirillum and AMF with 75 per cent dose of p.op. Azospirillum with 50 per cent POP also gave good results. Both these treatments were on par and was better than our state recommendation. Growth characters viz: Seedling growth rate, plant height, number of leaves per plant, number of branches per plant, LAI were highest. for Azospirillum inoculation at early stages. While AMF inoculation gave notable results at later stages. Physiological parameters namely Biomass, NAR, Root dry weight were significantly improved with dual inoculation and higher dose of chemical fertilizer. Leaf dry weight, RGR and CGR responded most to inoculation with Azospirillum at early stages, while at later stage AMF performed well. Kannara local was superior to